2022
DOI: 10.3390/brainsci12060801
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Music Therapy in the Reduction of Pre-Meal Anxiety in Patients Suffering from Anorexia Nervosa

Abstract: Literature reviews appear to indicate that Music Therapy (MT) may instil a sense of empowerment and generate feelings of renewed self-confidence, distracting subjects who follow this type of intervention from negative thoughts and, generally, helping patients suffering from Anorexia Nervosa (AN) to redevelop or rediscover their identity. The purpose of the study reported in this paper is to investigate whether MT proposed before an evening meal is capable of decreasing pre-meal anxiety in adolescents suffering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The study found improvements in not only anxiety after this weeklong intervention, but also in negative thinking [15]. Ceccato and Roveran studied a sample of adolescent females with anorexia nervosa and found improvements in pre-meal anxiety after group music therapy [19]. Additional reports from the study indicated that participants were spontaneously utilizing the music from the sessions on their own time, in order to relax or relive emotions from the group sessions [19].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The study found improvements in not only anxiety after this weeklong intervention, but also in negative thinking [15]. Ceccato and Roveran studied a sample of adolescent females with anorexia nervosa and found improvements in pre-meal anxiety after group music therapy [19]. Additional reports from the study indicated that participants were spontaneously utilizing the music from the sessions on their own time, in order to relax or relive emotions from the group sessions [19].…”
Section: Discussionmentioning
confidence: 93%
“…All six studies showed significant improvements in anxiety for adolescents and young adults receiving music therapy [14,15,16,17,18,19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations